Differential post-treatment outcomes of methylphenidate for smoking cessation for individuals with ADHD - Luo, Sean X. (Am J Addict, 2019)
BACKGROUND AND OBJECTIVES: In a multisite, randomized study (CTN-0029), a 3-month course of osmotic-release oral system methylphenidate (OROS-MPH) improved smoking cessation in a group of patients with higher baseline severity in Attention-Deficit/Hyperactivity Disorder (ADHD). This treatment, however, worsened smoking cessation outcome in the group with lower baseline ADHD severity. We want to examine whether this differential treatment effect persisted after OROS-MPH was discontinued. METHOD: We conducted a secondary analysis of the 1-month follow-up data from CTN-0029 after the discontinuation of OROS-MPH (N=134). Nicotine patch was tapered during this month. We tested whether OROS-MPH had an effect on self-reported 7-day abstinence by week, as well as possible treatment by baseline ADHD severity interactions. RESULTS: Abstinence diminished overall in time after the end of the treatment. In the high baseline severity group, patients who received OROS-MPH had an advantage in 7-day abstinence at week 15 (40% for OROS-MPH vs. 20% for placebo, OR = 2.63, p = 0.028). In the lower severity group (n=121), no difference was detected (29% for OROS-MPH vs. 32% for placebo, p = 1.00) between the two treatment groups. There was also a significant treatment by baseline ADHD severity interaction (p=0.03). CONCLUSIONS AND SCIENTIFIC SIGNIFICANCE: OROS-MPH promotes abstinence beyond the course of treatment for patients with more severe ADHD, while the paradoxical effects in the lower baseline severity group is not persistent after medication discontinuation. Targeting ADHD in smoking cessation as a co-morbidity therefore can have broader impact with more precise patient selection.